Importance of IL‐6 inhibition in prevention and treatment of antibody‐mediated rejection in kidney allografts. (1st December 2022) - Jordan, Stanley C.; Ammerman, Noriko; Huang, Edmund; Vo, Ashley
Abstract : Interleukin‐6 (IL‐6) is a cytokine critical for innate and adaptive immune responses. However, persistent expression of high levels of IL‐6 are associated with a number of pathologic conditions including autoimmune diseases and capillary leak syndrome. Importantly, in kidney transplant patients, IL‐6 may play a role in mediation of cell‐mediated rejection (CMR) and antibody‐mediated rejection (AMR). This is likely due to the importance of IL‐6 in stimulating B cell responses with pathogenic donor‐specific antibody (DSA) generation and stimulation of T effector cell responses while inhibiting T regulatory cells. Data from preliminary clinical trials and clinical observations show that tocilizumab (anti–IL‐6R) and clazakizumab (anti–IL‐6) may have promise in treatment of CMR, AMR and chronic (cAMR). This has led to a phase 3 placebo, randomized clinical trial of clazakizumab for treatment of cAMR, a condition for which there is currently no treatment. The identification of IL‐6 production in vascular endothelia cells after alloimmune activation reveals another potential pathway for vasculitis as endothelia cell IL‐6 may stimulate immune cell responses that are potentially inhibitable with anti–IL‐6/IL‐6R treatment. Importantly, anti–IL‐6/IL‐6R treatments have shown the ability to induce Treg and Breg cells in vivo which may have potential importance for prevention and treatment of DSA development and allograft rejection.